Determination of N-(2-hydroxyethyl)valine in globin of ethylene oxide-exposed workers using total acidic hydrolysis and HPLC-ESI-MS2 - Mráz, Jaroslav; Hanzlíková, Iveta; Dušková, Šárka; Tvrdíková, Monika; Chrástecká, Hana; Vajtrová, Radka; Linhart, Igor (Toxicology letters, 2018)
Ethylene oxide (EO), an industrial intermediate and gaseous sterilant for medical devices, is carcinogenic to humans, which warrants minimization of exposure in the workplaces. The principal analytical strategy currently used in biomonitoring of exposure to EO consists in the conversion of N-(2-hydroxyethyl) adduct at the N-terminal valine (HEV) in globin to a specific thiohydantoin derivative accessible to GC-MS analysis (modified Edman degradation, MED). Though highly sensitive, the method is laborious and, at least in our hands, not sufficiently robust. Here we developed an alternative strategy of HEV determination based on acidic hydrolysis (AH) of globin followed directly by HPLC-ESI-MS2 analysis. Limit of quantitation is ca. 25 pmol HEV/g globin. Comparative analyses of globin samples from EO-exposed workers by both the AH-based and MED-based methods provided results that correlated well with each other (R2 > 0.95) but those obtained with AH were significantly more accurate (according to external quality control programme G-EQUAS) and repeatible (5% and 6% for intra-day and between-day analyses, respectively). In conclusion, the new AH-based method surpassed MED being similarly sensitive, much less laborious and more reliable, thus applicable as an effective tool for biomonitoring of EO in exposure control and risk assessment.
Keywords: Ethylene oxide; Environmental Biomarkers; hodnocení rizik; Ethylene Oxide; ethylenoxid; Valine; hydrolýza; Biological monitoring; bioindikátory; monitorování životního prostředí; Occupational Health; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; lidé; Occupational Exposure; Risk Assessment; inhalační expozice; Protein hydrolysis; Globin adducts; N-(2-Hydroxyethyl)valine; hmotnostní spektrometrie s elektrosprejovou ionizací; reprodukovatelnost výsledků; Chromatography, High Pressure Liquid; kyseliny; globiny; Male; valin; pracovní expozice; Hydrolysis; Environmental Monitoring; Globins; hygiena práce; mužské pohlaví; Spectrometry, Mass, Electrospray Ionization; Inhalation Exposure; Acids; Humans